Subarctic catchment water storage and carbon cycling – leading the way for future studies using integrated datasets at Pallas, Finland - Marttila, Hannu; Lohila, Annalea; Ala‐Aho, Pertti; Noor, Kashif; Welker, Jeffrey M.; Croghan, Danny; Mustonen, Kaisa; Meriö, Leo‐Juhani; Autio, Anna; Muhic, Filip; Bailey, Hannah; Aurela, Mika; et al.
2021